Health‐related quality of life and patient burden in patients with split‐thickness skin graft donor site wounds. Issue 2 (15th December 2017) - Humrich, Marco; Goepel, Lisa; Gutknecht, Mandy; Lohrberg, David; Blessmann, Marco; Bruning, Guido; Diener, Holger; Dissemond, Joachim; Hartmann, Bernd; Augustin, Matthias
Abstract : Split‐thickness skin grafting is a common procedure to treat different kinds of wounds. This systematic, multicentre, observational, cross‐sectional study of adult patients with split‐thickness skin graft (STSG) donor site wounds was conducted to evaluate quality of life (QoL) impairments caused by donor site wounds following split‐thickness skin grafting. Therefore, 112 patients from 12 wound centres in Germany were examined based on patient and physician questionnaires as well as a physical examination of the donor site wound. Most indications for skin grafting were postsurgical treatment (n = 51; 42.5%) and chronic wounds (n = 47; 39.2%). European QoL visual analoque scale (EQ VAS) averaged 64.7 ± 23.3, European QoL 5 dimensions (EQ‐5D) averaged 77.4 ± 30.0. Wound‐QoL (range: 0‐4) was rated 0.8 ± 0.8 post‐surgery and 0.4 ± 0.6 at the time of survey (on average 21 weeks between the time points). Compared to averaged Wound‐QoL scores of chronic wounds donor site‐related QoL impairments in split‐thickness skin‐graft patients were less pronounced. There were significant differences in patient burden immediately after surgery compared to the time of the survey, with medium effect sizes. This supports the hypothesis that faster healing of the donor site wound leads to more favourable patient‐reported outcomes.